Pavement material and technology elements in green highway rating systems-a conspectus - Bujang, Mastura; Hainin, Mohd Rosli; Yadollahi, Mohammadreza; Abd. Majid, Muhd Zaimi; Mohamad Zin, Rosli; Wan Azahar, Wan Nur Aifa (UTM Press, 2014)
Since the effect of global warming and climate changes are becoming serious issues nowadays, most countries are trying to develop their own green highway rating system in order to implement the sustainable practices on their highway.Several studies have discussed the issues relating to the sustainable rating system, but no major study has been conducted to examine the green highway rating system in depth.Material and pavement technology are two most important parameters in the green highway rating systems and need to be addressed more critically. This study presents an extensive review to identify and establish the material and pavement technology elements that are most appropriate to be considered in developing the green highway rating systems.The relevant literatures have been reviewed to assist in identifying the elements of material and pavement technology. These elements in existing green highway rating systems are tabulated and ranked to show the importance level of each element. Understanding the comparison between these elements in existing green highway rating systems would help in identifying and overcoming the scarcity of the elements. Subsequently, the complete highway rating system can be developed as a performance measure or baseline reference that suit different environment and weather. The result shows that themost appropriate elements in material and pavement technology in highway development are recycled materials and regional materials.These elements could optimize the sustainable designs, encourage the usage of recycled materials, and minimize the transportation that help in reducing pollution and energy consumption.